Digital Nomad Workstyle and Its Effect on Task Completion and Time Management - Ismi Iftikad; Tomo Hardiyanto; Aldy Rostyawan (Universitas Negeri Surabaya, 2026)
The digital nomad workstyle, characterized by location-independent work enabled by digital technologies, has emerged as a significant phenomenon in the contemporary labor market. This article examines the effects of digital nomadism on task completion and time management, synthesizing findings from recent empirical research. The analysis reveals that productivity among digital nomads depends less on workload volume and more on how work is structured and controlled. Digital nomads who actively shape their tasks and schedules perceive themselves as more productive, consistent with job crafting theory. However, the flexibility inherent in the digital nomad lifestyle presents dual edged implications: while autonomy can enhance task engagement and satisfaction, the absence of traditional organizational structures creates significant time management challenges, including increased susceptibility to procrastination, difficulty establishing work life boundaries, and complications arising from multiple time zones. Effective time management strategies—including structured routines, time blocking, the Pomodoro Technique, and digital accountability tools—emerge as critical mediators between the nomadic workstyle and successful task completion. The findings suggest that the digital nomad workstyle's effect on productivity is contingent upon individuals' self regulatory capacities and their deliberate implementation of structuring practices.